TINGKAT KEPUASAN KONSUMEN TERHADAP SISTEM PEMESANAN TIKET ONLINE PADA MASKAPAI GARUDA INDONESIA DI DENPASAR BALI - Ayu Savitri, Ni Putu; Suardana, I Wayan; Sudiarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 2 No 1 (2014): Jurnal IPTA (July 2014), 2014)
This study discsess the level of the research about the level of customer satisfaction with the online ticket booking system on Garuda Indonesia in Denpasar Bali. This study aims to determine user satisfaction online ticket booking system. The research method used is the Cartesian diagram. These results indicate that the level of customer satisfaction was 88.68%. It can be concluded that consumers were less satisfied with the performance or services provided from an online ticket booking system suitability Garuda Indonesia karen prsentase not be above 100% or equal to 100%. Based on the characteristics can be in simpulakan that 62.5% of consumers men - men and 45% of consumers are over 45 years old. Based on these results, it can be concluded some suggestions that can be beneficial for the airline Garuda Indonesia there; ah as follows: to put the choice should request special ntuk with disabilities as can order service korsi wheel when booking tickets online. Because Garuda Indonesia is not included in the ticket booking system guarantees and insurance ll clarify what is in the can and that the rights of every passenger.
Keywords: Satisfaction, Customer, Service Quality